A Technological Solution to Supervise CoViD-19 Symptoms in Senior Patients in Lima - Haro-Hoyo, Sara (2023)
The article’s objective is to outline the application of a technological solution based on wearable technology that provides for the best possible monitoring of elderly patients with CoViD19. This is a pressing issue right now because the epidemic has caused numerous problems for senior patients. For example, because older persons are more susceptible to CoViD19, they must limit social contact or adhere to stricter lockdown protocols. In order to do this, a thorough assessment of the relevant scientific literature in the phases of planning, development, and analysis was conducted. The use of technology models in real time, the monitoring of CoViD19 symptoms, and the usage of IoT for geriatric patient monitoring are all topics covered in this paper. Our findings demonstrate the viability of our strategy.